2023
DOI: 10.4103/ijves.ijves_37_23
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT for Teachers: Practical Examples for Utilizing Artificial Intelligence for Educational Purposes

Abstract: Background: Artificial intelligence (AI), specifically ChatGPT, has the potential to revolutionize medical education by acting as an interactive virtual tutor and personalized learning assistant. It may help both teachers and students in various ways. Objective: The objective of this article is to provide practical examples of the utilization of ChatGPT for educational purposes in the context of teaching. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…To fully realize these benefits, educators and institutions in developing countries need to invest in faculty development and carefully integrate LLMs into their curricula, thereby harnessing the advantages while mitigating associated risks in medical education. Figure 2 summarizes the domains where LLMs can be used in medical education [19,20]. A key limitation of this study is its reliance on self-reported data from medical students, which may introduce response bias.…”
Section: Discussionmentioning
confidence: 99%
“…To fully realize these benefits, educators and institutions in developing countries need to invest in faculty development and carefully integrate LLMs into their curricula, thereby harnessing the advantages while mitigating associated risks in medical education. Figure 2 summarizes the domains where LLMs can be used in medical education [19,20]. A key limitation of this study is its reliance on self-reported data from medical students, which may introduce response bias.…”
Section: Discussionmentioning
confidence: 99%
“…ChatGPT could also become a useful tool for teachers to manage various tasks such as teaching content generation, lesson planning, student assessment and grading (Mondal et al, 2023). Earlier research showed that ChatGPT is capable of offering comprehensive and creative lesson plans (Farrokhnia et al, 2023;Karakose et al, 2023a;Whalen & Mouza, 2023), generating a range of slides for classroom presentations with texts adjusted for students with different age or level (Herft, 2023;Mondal et al, 2023), facilitating their teaching through new ideas and strategies to teach (Luo et al, 2023), and aiding to design customized materials and content in accordance with the course or student requirements (Mondal et al, 2023;Zai, 2023).…”
Section: Chatgpt As a Teacher Aidementioning
confidence: 99%
“…153 One of the key components of ChatGPT's teacher professional development strategy is the provision of quick and easy access to relevant educational information and resources. ChatGPT serves as a highly adaptive virtual assistant to teachers, providing them with comprehensive guidance and referrals on the latest developments in teaching methods, current curriculum, effective classroom management strategies, and other aspects of education [23]. In practice, this innovation allows teachers to develop their knowledge continuously without having to spend valuable time manually searching for information.…”
Section: Journal Of Contemporary Administration and Management (Adman)mentioning
confidence: 99%